Women Entrepreneurship in Indian Context: A Critical Study of Its Problems and Solutions: Addressing Challenges and Promoting Women Entrepreneurship in India (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Entrepreneurship amongst nationals of a country contributes immensely towards the growth process of a country. Enterprising nature and spirit of entrepreneurship exists in all human beings irrespective of gender. A country’s economic growth would be imbalanced without the involvement of women in entrepreneurial activities. Today’s entrepreneurship domain is without any gender bias. In India, since 1991, women entrepreneurs are gaining huge importance, and they are being supported and encouraged by family, financial institutions and other stakeholders. Policy makers in India have formulated and implemented policies and schemes that promote the spirit of women entrepreneurship. Several training and development programmes have widened the horizon for economic empowerment of women in India. Besides the government, many other stakeholders need to play an important role in providing skill training, vocational education and in entrepreneurial development of women. Though women contribute only one third of the economic enterprises, a large proportionate of women entrepreneurs have successfully established themselves in social and economic fields in India. Despite the growing pace of women enterprises, the rising unemployment, poverty and disparity in the economic status of women, has led to the growth of women entrepreneurship becoming increasingly challenging. This paper seeks to analyse the issues, problems and challenges encountered by the women entrepreneurs and also suggests measures to overcome them.